From Clicks to Conversions: The Impact of Viral Marketing on Tourism Branding - Martha Gegung, Eunike (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This article explores the significance of viral marketing and how it impacts tourism branding and affects travelers' behaviors from clicks to trips. It uses three themes: destination image, traveler engagement, authenticity, and how it influences travel intention. A qualitative approach is used to uncover insights, while a thematic analysis is used to look for patterns that emerge from the data. The results reveal that strategic use of social media platforms and user-generated content (UGC) of destinations can craft authentic and compelling narratives that resonate with travelers, enhancing destinations' visibility and appeal. The research also highlights the dual nature of viral marketing; while it can significantly boost a destination's desirability by showcasing cultural attractions and positive visitor experiences, it also presents risks, as poorly managed campaigns can lead to negative publicity and damage a destination's reputation. Some examples of viral campaigns illustrate the potential benefits and challenges of viral marketing. The study concludes that successful viral marketing requires a careful balance of authenticity, emotional engagement, and consistent information, enabling tourism brands to build lasting relationships with visitors. However, as viral content continues to shape perceptions, destinations must manage their online reputation effectively to ensure their brand promise is consistently upheld.